Insights from a Box-Behnken Optimization Study of Microemulsions with Salicylic Acid for Acne Therapy - Maria-Cristina Anicescu; Cristina-Elen; Marina-Theodora Talianu; Mihaela Violeta Ghica; Valentina Anuța; Răzvan-Mihai Prisada; Anca Cecilia Nicoară; Lăcrămioara Popa (MDPI AG, 2022)
The present study brings to attention a method to develop salicylic acid-based oil in water (O/W) microemulsions using a tensioactive system based on Tween 80, lecithin, and propylene glycol (PG), enriched with a vegetable oat oil phase and hyaluronic acid. The systems were physically characterized and the Quality by design approach was applied to optimize the attributes of microemulsions using Box-Behnken modeling, combined with response surface methodology. For this purpose, a 33 fractional factorial design was selected. The effect of independent variables namely X1: Tween 80/PG (%), X2: Lecithin (%), X3: Oil phase (%) was analyzed considering their impact upon the internal structure and evaluated parameters chosen as dependent factors: viscosity, mean droplet size, and work of adhesion. A high viscosity, a low droplet size, an adequate wettability-with a reduced mechanical work-and clarity were considered as desirable for the optimal systems. It was found that the optimal microemulsion which complied with the established conditions was based on: Tween 80/PG 40%, lecithin 0.3%, oat oil 2%, salicylic acid 0.5%, hyaluronic acid 1%, and water 56.2%. The response surface methodology was considered an appropriate tool to explain the impact of formulation factors on the physical properties of microemulsions, offering a complex pattern in the assessment of stability and quality attributes for the optimized formulation.